Clinical outcomes of dogs with high-grade cutaneous mast cell tumors - Ong, Siew Mei; McKenna, Charly; Pinard, Christopher; Richardson, Danielle; Oblak, Michelle L. (Frontiers in Veterinary Science, 2025)
ObjectivesTo evaluate the prognostic factors and treatment outcomes in dogs with high-grade cutaneous mast cell tumors (HGMCTs).MethodsMedical records of dogs with a histopathologic diagnosis of HGMCTs were reviewed from a single institution. Clinical factors, treatment-related variables, and adjuvant therapies were documented to evaluate their association with clinical outcomes. Comparative and survival analyses were conducted using Kaplan–Meier survival analysis, log-rank, and Fisher’s exact tests.ResultsThe overall median survival time for the 77 dogs was 317 days (range 20–3,041 days) with 6-month, 1-year, and 2-year survival rates of 69, 50, and 30%, respectively. Surgically treated dogs had significantly prolonged survival and were 6.88 times more likely to survive beyond 5.5 months. The presence of metastasis at initial staging was strongly associated with poorer outcomes, as dogs without metastasis at initial staging had 6.94 times higher odds of surviving beyond 2 years. Surgical sites with incomplete margins had a higher local recurrence rate (58%) compared to those with clean margins (26%). Despite aggressive treatment, 75% of the dogs that received concurrent surgical and adjuvant therapy experienced disease progression. Lymph node extirpation, tumor localization, number of tumors, and local recurrence were not associated with the overall outcome.Clinical relevanceThe combination of aggressive local therapy and adjuvant systemic chemotherapy provides a notable survival benefit in dogs with HGMCTs. The limited therapeutic benefit of locoregional lymph node extirpation, combined with a persistently high metastatic rate despite systemic chemotherapy, highlights the critical need for more effective regional and systemic treatment approaches for HGMCT patients.